Penerapan Media Sosial bagi Peningkatan Kinerja UMKM di Kota Jambi - Firdaus Firdaus; Fahrizal Fahrizal (Universitas Batanghari Jambi, 2021)
The purpose of this study is to describe the role of social media and small and medium micro enterprises performance in Jambi City, as well as the influence of the role of social media on business performance. The research data were obtained through a survey method using a questionnaire given to 60 respondents. The data is analyzed using simple linear regression analysis techniques. The analysis shows that the role of social media, which is reflected by the dimensions of curation, consumption, creation, and collaboration as a whole get an average score acquisition in the range of 3.41-4.20 with